2020
DOI: 10.1155/2020/4957238
|View full text |Cite
|
Sign up to set email alerts
|

Diazoxide Protects against Myocardial Ischemia/Reperfusion Injury by Moderating ERS via Regulation of the miR-10a/IRE1 Pathway

Abstract: Nowadays, reperfusion is still the most effective treatment for ischemic heart disease. However, cardiac reperfusion therapy would lead to reperfusion injury, which may have resulted from endoplasmic reticulum stress (ERS) during reperfusion. Diazoxide (DZ) is a highly selective mitochondrial adenosine triphosphate-sensitive potassium channel opener. Its protective effect on I/R injury has been confirmed in many organs such as the heart and brain. However, the mechanism of its protective effect has not been fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Recent studies showed that multiple mechanisms are involved during the process of myocardial I/R injury, such as inflammation, apoptosis, intracellular calcium overload, endothelial dysfunction, reactive oxygen species, and endoplasmic reticulum stress (ERS). [3][4][5][6][7][8] Under physiological conditions, the endoplasmic reticulum serves many essential roles in cell function, including protein synthesis, protein folding, calcium homoeostasis, and lipid metabolism. 8,9 Under a stress condition such as the myocardial I/R process, the endoplasmic reticulum homoeostasis is disrupted, and unfolded or misfolded proteins accumulates, leading to the prolonged unfolded protein response (UPR) during ERS.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that multiple mechanisms are involved during the process of myocardial I/R injury, such as inflammation, apoptosis, intracellular calcium overload, endothelial dysfunction, reactive oxygen species, and endoplasmic reticulum stress (ERS). [3][4][5][6][7][8] Under physiological conditions, the endoplasmic reticulum serves many essential roles in cell function, including protein synthesis, protein folding, calcium homoeostasis, and lipid metabolism. 8,9 Under a stress condition such as the myocardial I/R process, the endoplasmic reticulum homoeostasis is disrupted, and unfolded or misfolded proteins accumulates, leading to the prolonged unfolded protein response (UPR) during ERS.…”
Section: Introductionmentioning
confidence: 99%
“…qPCR detection showed that the expression of IRE1 mRNA was not affected, suggesting that IRE1 is post-transcriptionally regulated by miR-10a. This reveals that miR-10a promotes myocardial I/R injury by down-regulating the ERS-related protein IRE1, which provides a theoretical basis for preventing I/R myocardial injury and apoptosis [ 78 ].…”
Section: Microrna Regulates Ers-mediated Apoptosismentioning
confidence: 99%
“…The miRNAs are critical modulators of ER stress homeostasis and UPR signaling, so, targeting these miRNAs could serve as a potential therapeutic approach. MiR‐10a exerts a suppressive impact on the IRE1 expression, and miR‐10a inhibitor up‐regulates the IREl‐XBP1 signaling pathway in cardiomyocytes, thereby relieving myocardial I/R injury (L. Zhang et al, 2020). MiR‐199a‐5p is significantly downmodulated in myocardial tissue from individuals with CCHD.…”
Section: Therapeutic Approaches On the Basis Of The Upr And Ncrnas In...mentioning
confidence: 99%